Developing a national trauma research action plan: Results from the Burn Research Gap Delphi Survey. Issue 1 (January 2022) - Gibran, Nicole S.; Shipper, Edward; Phuong, Jimmy; Braverman, Max; Bixby, Pam; Price, Michelle A.; Bulger, Eileen M.
Abstract : BACKGROUND: The 2016 National Academies of Science, Engineering and Medicine call for a national integrated, military-civilian trauma action plan to achieve zero preventable deaths and disability after injury included a proposal to establish a National Trauma Research Action Plan to "strengthen trauma research and ensure that the resources available for this research are commensurate with the importance of injury and the potential for improvement in patient outcomes." The Department of Defense funded the Coalition for National Trauma Research to generate a comprehensive research agenda spanning the continuum of trauma/burn care from prehospital to rehabilitation. The Burn/Reconstructive Surgery group represents one focus area for this research agenda development. METHODS: Experts in burn and reconstructive surgery research identified gaps in knowledge, generated research questions and prioritized questions using a consensus driven Delphi survey approach. Participants were identified using established Delphi recruitment guidelines to ensure heterogeneity and generalizability with military and civilian representatives. Literature reviews informed the panel. Panelists were encouraged to use a PICO format to generate research questions: P atient/Population; I ntervention; C ompare/Control; O utcome. Participants ranked the priority of each question on a nine-point Likert scale, which was categorized to represent low, medium, and high priority items. Consensus was defined based on ≥60% panelist agreement. RESULTS: Subject matter experts generated 949 research questions in 29 Burn & 26 Reconstruction topics. Five hundred ninety-seven questions reached consensus. Of these, 338 (57%) were high-priority, 180 (30%), medium-priority, and 78 (13%) low-priority questions. CONCLUSION: Many high-priority questions translate to complex wound management and outcomes. Panel recognition that significant gaps in knowledge exist in understanding functional outcomes after injury underscores the importance of long-term recovery metrics even when studying acute injury or interventions such as resuscitation or inhalation injury. Funding agencies and burn/reconstructive surgery researchers should consider these gaps when they prioritize future research. LEVEL OF EVIDENCE: Expert consensus, Level IV. Abstract : Supplemental digital content is available in the text.